ANALYSIS OF FINANCIAL PERFORMANCE MANAGEMENT OF VILLAGE FUND ALLOCATION BASED ON EFFECTIVENESS AND GROWTH RATIO IN SUNGAI ARA VILLAGE 2020-2022 - SITI KARMILA; MUHAMMAD FAUZAN (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This study aims to find out how well the Financial Performance of Village Fund Allocation Management is based on the Effectiveness Ratio and Growth Ratio in Sungai Ara Village. The type of research used is a quantitative research type because the data collected is in the form of figures from the Village Fund Allocation (ADD) financial reports in the Village Revenue and Expenditure Budget from 2020-2022. Data collection techniques used are documentation techniques and literature studies. The data analysis technique used is to use a qualitative descriptive approach with the formula for the ratio of effectiveness and growth ratio. The results of the study indicate that in general the financial performance of the Sungai Ara Village Government has been good in managing the Village Fund Allocation finances. Where based on the ratio of the effectiveness of managing the Village Fund allocation for 2020-2022 it is categorized as effective. This shows that the ability of the Sungai Ara Village government to achieve the Village Fund target has been going well. Then based on the ratio of Village Fund income growth every year it fluctuates. However, if seen from the percentage of growth, it is still low every year. This shows that the ability of the Sungai Ara Village government to maintain and increase success in managing the Village Fund Allocation finances that have been achieved every year is still low. This means that the financial performance of Sungai Ara Village, Indragiri Hilir Regency, in terms of the management of Village Fund Allocations based on the growth ratio in 2020-2022, is in the low category.